# Projectile on the moon

1. Nov 15, 2009

### ryty

1. The problem statement, all variables and given/known data
A projectile launched vertically from the surface of the Moon rises to an altitude of 370 km. What was the projectiles initial speed?

2. Relevant equations
Vf ^2 = Vi^2 + 2ad

3. The attempt at a solution
distance = 370km x 1000 = 3.7E 5 meters
solving for Vi = sqroot of Vf^2 - 2ad
sqrt of 0 - -1.63 x 3.7E5 = 777m/s

2. Nov 15, 2009

### ideasrule

Check your calculations. 1.63 m/s^2 is equal to a, not 2a.

3. Nov 15, 2009

### ryty

alright, i tried this vi=sqrt(2(1.63)(3.7)=1098, but thats wrong too, i still cant find out what im doing wrong

4. Nov 16, 2009

### ideasrule

1098 m/s is correct, unless the problem wanted you to take into consideration differences in acceleration due to the object's increasing altitude.

5. Nov 16, 2009

### ryty

i dont know, my hw is online, so i just type in an answer, and it ells me whether im right or wrong, and it said i was wrong. So how would i compensate for the difference?

6. Nov 16, 2009

### ideasrule

You use the conservation of energy: initial kinetic energy + initial potential energy = final kinetic energy + final potential energy. Make sure to use U=-GMm/r for potential energy, not U=mgh.

7. Nov 16, 2009

### ryty

what masses should i use?

8. Nov 16, 2009

### ideasrule

Well, in U=-GMm/r, M and m are the two attracting masses. Here, one of them is the Moon and the other is the projectile. You'll find that the mass of the projectile cancels out, so you don't need to know what it is.

9. Nov 16, 2009

### ryty

10. Nov 16, 2009

### ideasrule

"r" is the distance from the center of the planet/moon to the projectile. So yes, you add the radius of the moon.

11. Nov 16, 2009

### ryty

i got 1.01 m/s, which is wrong
0 + G(6.67E-11*7.36E22)/21074000^2 = 1/2vi^2 + G(6.67E-11*7.36E22)/1737400^2

12. Nov 16, 2009

### willem2

It's U=-GMm/r not U=-GMm/r^2 f

13. Nov 16, 2009

### ryty

just for easier ways to put it Kf=a Uf=b Ki=c Ui=d
it should look like this
c= -b + d